Pengaruh Kinerja Staf Tata Usaha Terhadap Mutu Layanan Administrasi Guru di SMAN 2 Barru - waslia22 (Education Management: Jurnal Manajemen Pendidikan Islam (Edium), 2023)
Administrative staff performance is the result of work in a series of administrative activities over a certain period and perfected according to their responsibilities. School administration services are an important means of improving school quality. The role of administrative staff in the realm of school administration plays an important role. Teachers are responsible for tasks such as formulating policies and carrying out processes of planning, organizing, directing, coordinating, financing, and evaluating various aspects of the curriculum. This includes activities involving students, school infrastructure, school personnel, finances, and school-community relations. It is very important that teachers dedicate their energy and cognitive abilities to fulfill this responsibility.This study aims to determine the effect of administrative staff performance on the quality of teacher administration services at SMAN 2 Barru which was carried out in the quantitative research category. Data collection involved distributing questionnaires to participants. The Total Sampling method was used to determine the sample size. To test the hypothesis used simple linear regression analysis.The results of the study show that: in testing the regression coefficient through the t test with the acquisition of tcount = 8.331 and ttable = 2.007 at a significance level of 5%. The value obtained is tcount = 8.331 > from ttable = 2.007 with correlation coefficients r value obtained 0.759, and significant value = 0.000 <0.05, it is said that there is an effect of administrative staff performance on the quality of teacher administration services at SMAN 2 Barru with a strong relationship level.